Reference priors for discrete graphical models - Guido Consonni; Valentina Leucari (Università degli Studi di Pavia, Dipartimento di Economia Politica e Metodi Quantitativi (EPMQ), 2005)
The combination of graphical models and reference analysis represents a powerful tool for Bayesian inference in highly multivariate settings. It is typically difficult to derive reference priors in complex problems. In this paper we present a suitable mixed parameterisation for a discrete decomposable graphical model and derive the corresponding reference prior.
Keywords: 330; Decomposable model; Fisher information matrix; Mixed parameterisation; Natural exponential family; Bayes-Statistik; Inferenzstatistik